Unlocking Innovation Capacity: Strategies for Micro-, Small, and Medium Enterprises in Ukrainian Agriculture - Viktoriya Onegina; Lesia Kucher; Anatolii Kucher; Vitaliy Krupin; Marek Kłodziński; Vladyslav Logos (Agriculture)
Innovation is a crucial driver of competitiveness and development of enterprises. Access to innovation is influenced by a multitude of factors, including, among others, an enterprise’s strategy, operation efficiency, and the availability of resources. Middle, small, and micro-enterprises (MSMEs) are pivotal to agricultural production, employment, and food security in Ukraine; however, innovative technologies have predominantly been accessible to large enterprises. The aim of this study is to examine the innovation capacity of MSMEs in the Ukrainian agricultural sector and to identify potential strategies for integrating them to improve access to and inclusion of innovative practices. This study undertakes a quantitative evaluation of the innovation capacity of agricultural enterprises in Ukraine for the years 2019–2022, the latter marking the onset of wartime conditions. A comprehensive framework comprising indicators across technological, resource, financial, managerial, and human capital dimensions was developed to assess the innovation capacity of these enterprises. Utilizing data normalization techniques, composite indicators that offer a unified measure of innovation capacity were derived. Our findings substantiate the Schumpeterian hypothesis within the Ukrainian agricultural sector, revealing that MSMEs exhibit significantly lower innovation capacity compared to their larger counterparts, which causes serious problems with access to innovation. This disparity is particularly pronounced in terms of resources and technological capabilities, whereas the gap in financial performance and managerial and human capital is not significant. Conclusively, the recommendations on strengthening the innovative capacity of agricultural MSMEs—based on integration strategies—have been developed.